Electrochemical reduction and cathodic stripping voltammetric determination of clotrimazole - Pereira, Francisco C. [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Sociedade Brasileira de Química, 2001)
Clotrimazol é reduzido em eletrodo de mercúrio em tampão fosfato pH > 6 através de um processo reversível de um elétron. O processo eletródico apresenta forte efeito de adsorção, o qual pode ser minimizado na presença de Triton X-100. Clotrimazol pode ser determinado em níveis de 50 ng mL-1 quando pré-acumulado durante 3 min à -0,20 V. O método proposto foi aplicado para determinação do fármaco em formulação comercial.

The reduction of clotrimazole at a mercury electrode, in phosphate buffer, pH>6, involves a reversible one-electron process. The electrochemical process presents a large contribution from adsorption effects. For the differential pulse polarographic determination the addition of Triton X-100 is recommended. Clotrimazole can be determined by cathodic stripping voltammetry at 50 ng mL-1 level when pre-accumulated for 3 min at an accumulation potential of -0.20 V. The proposed method is applied successfully for the determination of clotrimazole in a commercial formulation.
Keywords: clotrimazole; cyclic voltammetry; differential pulse polarography; cathodic stripping voltammetry